Utilizing Cost and Quality Measures to Guide Fixation of MTP Arthritis. Issue 3 (14th September 2018) - Hogan, MaCalus; Chambers, Monique; LaBaze, Dukens; Yan, Alan; Porter, Jake
Category: Midfoot/Forefoot Introduction/Purpose: Severe hallux rigidus is the 2nd most common disorder of the 1st metatarsophalangeal (MTP) joint and is present on more than 44% of radiographs taken in those over 80 years of age. Arthrodesis has been the proposed method of fixation for 1st MTP pathology. However, joint preserving alternatives to fusion have also been proposed to maintain joint motion and due to the relatively high nonunion rate (5.4%). However, few reports have investigated if the risk of complications from a fusion impact daily activities and functional outcomes. As such, we investigated the cost and quality associated with treatment of severe MTP arthritis to determine the optimal surgical intervention. Methods: This was a retrospective review of 384 patients from a prospectively collected foot and ankle platform registry in a payor-provider healthcare system. Patients who underwent surgical intervention from July 2015 to November 2017 were identified by CPT codes for MPT arthrodesis (28750) and arthroplasty (28293) as well as key words "hallux" and "rigidus". Patient reported outcome scores were extracted from the medical records including SF12-M, SF12-P, FAAM, and a binary PASS score. Exclusion criteria included poly-trauma, neurological impairment, and revision procedures. The Mann-Whitney test was performed using Minitab 18 to compare procedure groups for the small samples without a normal distribution, and chi squared analysis was used to analyze the PASS score. Significance was defined by a p-value of <0.05. Additionally, cost data was gathered across the institution based on the previously mentioned CPT codes at the same institution, although statistical analysis was limited by reporting of average numbers. Results: A total of 35 patients met inclusion criteria, with 26 arthrodesis and 9 arthroplasty patients. The arthrodesis group had an average age of 63.4 and the arthroplasty group had an average age of 60.1. The arthrodesis group had higher post op scores in measures including SF12-M, SF12-P, FAAM, and PASS. The arthrodesis group also had greater increase in postoperative SF12-P, and FAAM compared to pre-op scores, with the arthroplasty having higher increase in SF12-M. Of these, the differences in PASS score (p=0.02) and the change in SF12-P were significant (p=0.05). Analysis of cost identified 25 logs of MTP arthroplasty with an average cost of $6, 538 per case and 79 logs of MTP arthrodesis with an average cost of $5, 086. Conclusion: This study suggests that patients treated with arthrodesis for 1st MTP arthritis have improved outcomes with greater cost containment. Although the PASS and SF-12 scores showed significant differences, all of the results including pain scores revealed greater improvement with arthrodesis, with the exception of the SF12 mental. The small cohorts in this study are a limitation, but these, results are consistent with the current literature. However, with both higher outcome scores and lower cost, arthrodesis appears to have significant advantages compared to arthroplasty and further studies can help guide clinical decision making in this patient population.